Відповідь:
S6 = -2405/9; S6 = 1820/9
Пояснення:
Sn = b1 *(q^n - 1)/(q - 1)
S3 = b1 * (q^3 - 1)/(q - 1)
195 = 135 * (q^3 - 1)/(q - 1)
(q^3 - 1)/(q - 1) = 195/135 = 39/27
(q - 1) * (q^2 + q + 1)/(q - 1) = 13/9
q^2 + q + 1 - 13/9 = 0
q^2 + q - 4/9 = 0
Розв'язуємо квадратне рівняння
D = 1 - 4 * (-4/9) = 25/9
q1 = (-1 - 5/3)/2 = -4/3
q2 = (-1 + 5/3)/2 = 1/3
S6 = 135 * (q^6 - 1)/(q - 1) = 135 * (q^3 - 1)*(q^3 + 1)/(q - 1) = 135 * (q - 1) * (q^2 + q + 1)*(q^3 + 1)/(q - 1) = 135 * (q^2 + q + 1)*(q^3 + 1)
1) S6 = 135 * ((-4/3)^2 - 4/3 + 1)*((-4/3)^3 + 1)
S6 = 135 * (16/9 - 4/3 + 1) * (-64/27 + 1)= 135 * (13/9)*(-37/27) = 5 * 13/9 * (-37) = -2405/9
2) S6 = 135 * ((1/3)^2 + 1/3 + 1)*((1/3)^3 + 1) = 135 * 13/9 * 28/27 = 5 * 13 * 28/9 = 1820/9
= =
20mn² - 15m²n 60m^2n^2 60m^2n^2
8 8+x^3-2x^2+2x^2-4x+4x-8 x^3
+ x² + 2x + 4==
x-2 x-2 x-2
b+3 b-1 b+3 b-1 b^2+3b-9b+9 (b-3)^2 b-3
= - = ==
9b-27 - b² - 3b 9(b-3) b(b-3) 9b(b-3) 9b(b-3) 9b